Orbital Air Embolism After Intravenous Injection. Issue 4 (December 2018) - Rossiter-Thornton, Michael; Varma, Aditya; Verma, Nitin; Hewitt, Alex W.
Abstract : Abstract: An asymptomatic air embolism in the right superior ophthalmic vein was discovered incidentally during a cerebral computed tomography, most likely due to a preceding intravenous fluid bolus. This case illustrates the potential risk of air emboli being propagated to the cerebral venous circulation during routine injections and fluid resuscitation.